Pencatatan Perkawinan Di Indonesia Dikaitkan Dengan Good Governance - Barzah Latupono (Faculty of Law, Universitas Pattimura, 2018)
Marriage registration carried out by marriage registrar employees is often not in accordance with the rules set out in the Act. The law requires that the marriage record be carried out if it has fulfilled the legal requirements for marriage. There are cases of marriages that do not meet the legal requirements of marriage and there are also marriages that meet the legal requirements of marriage but are not stated. State apparatus in various service sectors, especially those concerning the fulfillment of civil rights and basic needs of the community, must be carried out in accordance with the mandate of the 1945 Constitution. Marriage records, such as the making of National Identity Cards or Driving Permits, actually discuss public services that are the responsibility of the state. So that it should pay attention to the principle of good governance, one of which is to establish costs that are in accordance with the standard of living of the people and procedures that are not user-friendly.